The Nature of Homeless Media in Law No. 40 of 1999 on the Press: A Perspective from the Theory of Legal Certainty - Dian Arlesti Lukman; Prija Djatmika; Bambang Sugiri; Yuliati Yuliati (Baileo: Jurnal Sosial Humaniora, 2026)
This article examines the nature of homeless media in Law No. 40 of 1999 on the Press through the perspective of legal certainty theory. The research method used is normative legal research with legislative, conceptual, and comparative approaches. The results show that homeless media media entities that substantively perform journalistic functions but lack formal legal status under the Press Law are essentially entities experiencing normative dissonance: their functional capacity as journalistic actors exceeds the available legal recognition. This dissonance stems from three structural weaknesses in the Press Law: the institutional bias of the legal entity requirement in Article 9(2), the temporal limitations of the 1999 regulation, and the absence of a mechanism for gradual recognition. Using Fuller’s eight criteria of the “inner morality of law” as an analytical framework, this study identifies that these conditions violate the criteria of generality, clarity, and congruence, resulting in three-dimensional legal uncertainty: regarding rights, obligations, and dispute resolution forums. This study concludes that the issue of “homeless media” is fundamentally a regulatory failure to respond to the diversity of the digital media ecosystem, not merely a matter of non-compliance by media actors. A reformulation of the Press Law that prioritizes a recognition-based approach grounded in journalistic functions is an urgent constitutional necessity.